2011
DOI: 10.2310/8000.2011.100301
|View full text |Cite
|
Sign up to set email alerts
|

Are butyrophenones effective for the treatment of primary headache in the emergency department?

Abstract: Objectives: Butyrophenones have been reported to provide effective migraine relief in the emergency department (ED). We conducted a systematic review of the evidence for their use in the ED. Data source: We searched the Cochrane, Medline, Embase, and CINAHL databases. Study selection: Included studies were randomized trials of a parenteral butyrophenone (droperidol, haloperidol) versus placebo or a comparator in migraine or benign headache with results available in English. Study quality was determined using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Haloperidol was the most common adjuvant medication prescribed, on a scheduled and as-needed basis, due to its NMDA-blocking effects and its relief of symptoms associated with terminal disease. [41][42][43][44] Our approach of using low-dose methadone for palliative pain management offers the potential for large cost savings compared to more standard practices. The average total medication cost on our service was $2.76 per patient per day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haloperidol was the most common adjuvant medication prescribed, on a scheduled and as-needed basis, due to its NMDA-blocking effects and its relief of symptoms associated with terminal disease. [41][42][43][44] Our approach of using low-dose methadone for palliative pain management offers the potential for large cost savings compared to more standard practices. The average total medication cost on our service was $2.76 per patient per day.…”
Section: Discussionmentioning
confidence: 99%
“…21,55,56,57 Nonopioid adjuvant medications have not received much attention in palliative pain management, and do not traditionally include haloperidol for pain despite its potential NMDA-blocking effects. 17,[41][42][43][44] The traditional approach of opioid dose escalation has paradoxically resulted in a decrease in analgesic effect, mediated by two related mechanisms: desensitization of the antinociceptive opioid pathway due to receptor tolerance, and sensitization of the pronociceptive NMDA pathway as a compensatory response to opioid receptor stimulation. [18][19][20][21]27,[58][59][60][61][62][63] This syndrome of opioid-induced hyperalgesia results in an increased sensitivity to pain that is proportional to the dose and strength of the opiate used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, opioids are not as effective in the treatment of acute migraine as other agents, such as dihydroergotamine (DHE), 22 ketorolac, 22 butyrophenones, and the phenothiazines with more side effects. 8,[23][24] In a study comparing treatment with chlorpromazine and meperidine, chlorpromazine was more effective and patients receiving meperidine were more likely to need rescue medication. 8 Opioids may also render acute migraine medications, such as triptans, less effective 24 and may impair the effectiveness of migraine preventives.…”
Section: Opioidsmentioning
confidence: 99%
“…17 In benign headaches, droperidol was superior to prochlorperazine at a dose of 2.5 mg given intravenously or 5 mg given intramuscularly. 18 A 2011 systematic review of 3 studies by Leong and Kelly 19 confirmed that droperidol was more effective than opioids or prochlorperazine for headaches, without an increase in adverse events.…”
Section: Use Of Droperidol In the Emergency Departmentmentioning
confidence: 99%